Managing Socio-ecological Production Landscapes and Seascapes for Sustainable Communities in Asia Mapping and Navigating Stakeholders, Policy and Action - Saito, Osamu; Subramanian, Suneetha M.; Hashimoto, Shizuka; Takeuchi, Kazuhiko (Science for Sustainable Societies,, 2020)
This open access book presents up-to-date analyses of community-based approaches to sustainable resource management of SEPLS (socio-ecological production landscapes and seascapes) in areas where a harmonious relationship between the natural environment and the people who inhabit it is essential to ensure community and environmental well-being as well as to build resilience in the ecosystems that support this well-being. Understanding SEPLS and the forces of change that can weaken their resilience requires the integration of knowledge across a wide range of academic disciplines as well as from indigenous knowledge and experience. Moreover, given the wide variation in the socio-ecological makeup of SEPLS around the globe, as well as in their political and economic contexts, individual communities will be at the forefront of developing the measures appropriate for their unique circumstances. This in turn requires robust communication systems and broad participatory approaches. Sustainability science (SuS) research is highly integrated, participatory and solutions driven, and as such is well suited to the study of SEPLS. Through case studies, literature reviews and SuS analyses, the book explores various approaches to stakeholder participation, policy development and appropriate action for the future of SEPLS. It provides communities, researchers and decision-makers at various levels with new tools and strategies for exploring scenarios and creating future visions for sustainable societies.